2015
DOI: 10.5152/balkanmedj.2014.14529
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Modulated Radiotherapy versus 3-Dimensional Conformal Radiotherapy Strategies for Locally Advanced Non-Small-Cell Lung Cancer

Abstract: In the evolution of radiation oncology technology, improved planning and treatment delivery advanced from two-dimensional radiotherapy (2DRT) to three-dimensional conformal radiotherapy (3DCRT) two decades ago. In the last decade, intensity-modulated radiation therapy (IMRT) emerged in addition to daily image guidance and fourdimensional (4D) image-based motion management (1). Chemoradiotherapy, which was actually established mainly with a 2DRT trial-RTOG 9410, is the current standard of care in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Dose fractionation and 3-Dimensional conformal radiation therapy (3DCRT, using CT images) significantly improved radiation treatment ( 146 ). The development of multileaf collimators allowing modulation of the X-ray beam dose-rate led to intensity-modulated radiation therapy (IMRT, characterized by a static delivery) and volumetric-modulated arc therapy (VMAT, with a dynamic delivery), which improved the target volume accuracy and led to less organ toxicity ( 147 , 148 ).…”
Section: The Dna Damage Response and Immunotherapiesmentioning
confidence: 99%
“…Dose fractionation and 3-Dimensional conformal radiation therapy (3DCRT, using CT images) significantly improved radiation treatment ( 146 ). The development of multileaf collimators allowing modulation of the X-ray beam dose-rate led to intensity-modulated radiation therapy (IMRT, characterized by a static delivery) and volumetric-modulated arc therapy (VMAT, with a dynamic delivery), which improved the target volume accuracy and led to less organ toxicity ( 147 , 148 ).…”
Section: The Dna Damage Response and Immunotherapiesmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT) based treatment planning helps in this regard by both better tumour and nodal delineation, thus potentially sparing normal tissue. Multiple studies have shown dosimetric benefits of intensity modulated radiation therapy (IMRT) over 3-dimensional conformal radiotherapy (3D-CRT) but no overall survival benefit has been demonstrated [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Ambiguous target due to tumor motion has been considered as one of the main reasons for local failure of tumor control . Several studies have shown that escalating radiation dose to the primary tumor might improve local control of the tumor . However, an increase in the radiation dose must be balanced against an increased risk of radiation toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several studies have shown that escalating radiation dose to the primary tumor might improve local control of the tumor. [4][5][6][7] However, an increase in the radiation dose must be balanced against an increased risk of radi-This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. ation toxicity.…”
Section: Introductionmentioning
confidence: 99%